Food Insecurity and Financial Access during an Economic Recession: Evidence from the 2008 SIPP. Issue 2 (2nd April 2016) - Birkenmaier, Julie; Huang, Jin; Kim, Youngmi
ABSTRACT: This study examines the association between financial access, unemployment, and household food insecurity during the economic recession (N = 14, 417). The unbanked lack financial access to smooth their consumption during times of financial stress. The dependent variable is food insecurity, the independent variable is banked status, and unemployment experience is a moderator. The results of this study, using Survey of Income and Program Participation data, indicate financial access and unemployment are significantly related to food insecurity for the general population, but there is no evidence that financial access mitigates food hardship for the unemployed. Policy implications are discussed.